The E-university: From E-training to E-learning - Abid, A.; Mueen, A.; Chong, C. K.; Tan, M. K. (2005)
E-learning is an information and communication technology enabled mode of knowledge delivery. It has its root in corporate training. In the corporate world, information and communication technology (ICT) is widely used not only in business operations and management, but also in training.The corporate sector found that using ICT for training is viable, beneficial, and can be expanded out to the traditional institutions of higher learning.E-university was borne as the result of the partnership between the corporate and traditional university. The corporate provides the capital, as well as its technical know-how in carrying out the business; whereas the traditional university supplements it with the knowledge contents in the particular field.The hardware needed for an e-university is the computers and the network infrastructures. The hardware must work together with the software, which include LMS, LCMS and others.The e-learning industry is divided into three sectors: content, technology and service. Each sector contributes in its own way for the success of e-learning industry.E-learning is a business venture; therefore it is natural that ROI will be an important consideration for e-learning providers. E-university came to life with some fundamental issues: (i) the recognition of its programs, (ii) privacy and security, (iii) the position of academic staff, and (iv) the cultural changes that follow the E-university adoption. Some suggestions for the successful implementation of the E-university are put forward as a conclusion.